Delayed Diagnosis of X-linked Lymphoproliferative Syndrome Type 2 in a 17-year-old Male With Severe Crohn's Disease and Recurrent Skin Infections. Issue 3 (12th August 2021) - Zacharias, Stephanie A.; Seshadri, Priyanka; Hwang, Sharon; Baker, Laura; Powell, Jonathan; Fernando del Rosario, J.; Molle-Rios, Zarela
Abstract : X-linked lymphoproliferative syndrome type 2 (XLP2) is a rare genetic primary immunodeficiency disease caused by mutations in the XIAP gene that lead to deficiency of the X-linked inhibitor of apoptosis protein. XLP2 is characterized by dysregulated immune responses and can result in an inflammatory bowel disease (IBD)-like phenotype, a form of monogenic IBD. Patients with XLP2 often succumb to fulminant hemophagocytic lymphohistiocytosis or Epstein-Barr virus infections. Hematopoietic stem cell transplantation (HSCT) is currently the only definitive treatment for XLP2. We report an adolescent with a delayed diagnosis of XLP2 in the setting of severe Crohn's disease diagnosed at age 9 years and recurrent skin infections. He is under evaluation for HSCT. Gastroenterologists must recognize monogenic IBD in patients of all ages with severe disease and signs of an underlying primary immunodeficiency disease. Patients with suspected monogenic IBD should undergo immunologic and genetic analysis at diagnosis to initiate potentially life-saving treatment.